Europe after Maastricht— Have the monetary questions been settled? - Norbert Berthold (Intereconomics, 1992)
The decisions taken at Maastricht seem to have finally removed the obstacles to European monetary union. So have the monetary questions really been settled? Is the process of monetary convergence irreversible?
Keywords: 330; European Community